The Effect of Boundary Slip on the Transient Pulsatile Flow of a Modified Second-Grade Fluid - N. Khajohnsaksumeth; B. Wiwatanapataphee; Y. H. Wu (Abstract and Applied Analysis)
We investigate the effect of boundary slip on the transient pulsatile fluid flow through a vessel with body acceleration. The Fahraeus-Lindqvist effect, expressing the fluid behavior near the wall by the Newtonian fluid while in the core by a non-Newtonian fluid, is also taken into account. To describe the non-Newtonian behavior, we use the modified second-grade fluid model in which the viscosity and the normal stresses are represented in terms of the shear rate. The complete set of equations are then established and formulated in a dimensionless form. For a special case of the material parameter, we derive an analytical solution for the problem, while for the general case, we solve the problem numerically. Our subsequent analytical and numerical results show that the slip parameter has a very significant influence on the velocity profile and also on the convergence rate of the numerical solutions.